2014
DOI: 10.15416/ijcp.2014.3.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Checklist Usage as a Guidance on Read-Back Reducing the Potential Risk of Medication Error

Abstract: AbstrakRumah sakit sebagai lini terakhir pelayanan kesehatan berkewajiban memberikan pelayanan berkualitas dan beorientasi pada keselamatan pasien, salah satunya tanggung jawab dalam mencegah medication error. Kolaborasi dan komunikasi yang efektif antar profesi dibutuhkan demi tercapainya keselamatan pasien. Read-back merupakan salah satu cara dalam melakukan komunikasi efektif. Before-after study dengan pendekatan TQM PDCA. Sampel adalah catatan obat pada rekam medik pasien rawat inap RSUP Sanglah pada mingg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Therefore, more interventions are needed to prevent medication errors. The results of this study are consistent with the findings of (Maharjana et al, 2014) which showed that the use of read-back guidance with checklists as a form of effective communication can reduce medication record filling errors in medical records that have the potential to cause medication errors, with a decrease from 45.54% to 10.17%.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, more interventions are needed to prevent medication errors. The results of this study are consistent with the findings of (Maharjana et al, 2014) which showed that the use of read-back guidance with checklists as a form of effective communication can reduce medication record filling errors in medical records that have the potential to cause medication errors, with a decrease from 45.54% to 10.17%.…”
Section: Resultssupporting
confidence: 90%